2020
DOI: 10.3389/fpls.2020.571912
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study and Identification of Candidate Genes for Nitrogen Use Efficiency in Barley (Hordeum vulgare L.)

Abstract: Nitrogen (N) fertilizer is largely responsible for barley grain yield potential and quality, yet excessive application leads to environmental pollution and high production costs. Therefore, efficient use of N is fundamental for sustainable agriculture. In the present study, we investigated the performance of 282 barley accessions through hydroponic screening using optimal and low NH 4 NO 3 treatments. Low-N treatment led to an average shoot dry weight reduction of 50%, but there were significant genotypic diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 84 publications
1
26
1
Order By: Relevance
“…Completely randomised design with three replications was used and the experiments were repeated four times. The solution in each tank was replaced after seven days and the pH adjusted to 6.5 through addition of NaOH and/or HCl [31].…”
Section: Seedling Survival and Vigour Evaluationmentioning
confidence: 99%
“…Completely randomised design with three replications was used and the experiments were repeated four times. The solution in each tank was replaced after seven days and the pH adjusted to 6.5 through addition of NaOH and/or HCl [31].…”
Section: Seedling Survival and Vigour Evaluationmentioning
confidence: 99%
“…Indeed, at the time of harvest, i.e., 14 days after sowing, most of the metabolic processes may have been adjusted and stabilized under LN and HN. Among the genes found to be commonly up-regulated, the putative nitrate transporter coding gene HvNRT2.10 (HORVUHrG098550) orthologous to the Arabidopsis AtNRT2.7 gene, is of particular interest since it was found in a QTL mapping study as involved in barley tolerance to low N (Karunarathne et al, 2020). This gene is closely related to OsNRT2.4 (Guo et al, 2020) which encodes a dual affinity nitrate transporter and was found to be involved in rice N nutrition although no phenotype was found for the knockout mutant (Wei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, nitrogen fertilization impacts plant tolerance to abiotic and biotic stresses (Fagard et al, 2014;Abid et al, 2016;Mur et al, 2017;Ding et al, 2018;Verly et al, 2020). The genetic diversity in terms of barley tolerance to nitrogen starvation has been explored (Oscarsson et al, 1998;Górny, 2001;Sinebo et al, 2004;Quan et al, 2016Quan et al, , 2019Karunarathne et al, 2020). However few data are available concerning the diversity of molecular responses of barley to nitrogen limitation (Møller et al, 2011;Quan et al, 2016Quan et al, , 2019Karunarathne et al, 2020Karunarathne et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of these studies was demonstrated in a recent study of GWAS developed in wild and domesticated accessions of barley, allowing to identify markers trait associations conferring efficient nitrogen use. HvNRT2.7 was identified as a promising candidate to increase the dry weight of the root and shoot and became a potential target for genetic improvement in this species [ 103 ]. In addition, for the pleiotropic effects of the NRT2 and NRT3 gene families, recent findings indicate that the genetic basis of efficient transport of nitrate involves these transporters among a pyramid of several genes that must be ranked to achieve the most effective approach that allows a satisfactory NUE level in the field [ 104 ] In rice crops, it has been shown that the overexpression of the OsNRT2.3b transporter increases the NUE, but this response improves if this transporter is introduced together with the promoter OsNAR2.1p.…”
Section: Discussionmentioning
confidence: 99%